Analysis Of Generation Z’s Online Medication Purchasing Behavior - Restu Saputra; Budi Sumaryono (International Journal of Health Engineering and Technology, 2026)
The digital age has transformed the way Generation Z (Gen Z) accesses healthcare services, including obtaining medications. The phenomenon of “kereta kuning” purchasing medications through e-commerce platforms and social media has become a significant trend due to its convenience, privacy, and competitive prices. However, this convenience poses serious health risks. This article aims to provide a narrative review of online medication purchasing behavior among Gen Z and its impact on patient safety. We conducted a literature review by collecting scientific journals from leading platforms such as Google Scholar, CrossRef, and PubMed in English. Analysis of the literature reveals that low digital health literacy and a tendency to self-diagnose based on viral content are driving Gen Z to consume prescription medications without medical supervision. Key risks include the circulation of substandard or counterfeit drugs, a lack of accurate dosage information, and the absence of pharmacists in clinical screening. Although digital access offers efficiency, without strict regulations and adaptive education tailored to Gen Z’s lifestyle, this trend could become a public health “disaster” in the future.